Metastatic Small Bowel Adenocarcinoma Mimicking a Primary Ovarian Mucinous Tumour – Clinical, Radiologic, Pathologic and Molecular Correlation. (February 2023) - Yang, Hang; Yuan, Ren; Alex, Deepu; Hughesman, Curtis; Liu, Shiru; Lee, Ursula; Zhou, Chen; Wang, Gang
We describe an interesting case of a patient who presented with a large adnexal mass, first favored to be mucinous carcinoma of the gynecologic origin. The primary tumour site was ascertained after the patient's small bowel was resected by identifying an adenomatous component evolving into an invasive adenocarcinoma identical in morphology and immunophenotype to the ovarian tumour. Notably, both tumours were found to harbor a BRAF K601E mutation, which is extremely rare for a primary of the ovary. BRAF mutations are present in a subset of large bowel and small bowel adenocarcinoma, but our case shows the first instance of a BRAF K601E mutation being present in a small bowel adenocarcinoma, to the best of our knowledge. This case serves as a great illustration of the pivotal role of molecular diagnostics in modern pathology in arriving at the correct diagnosis. Additionally, it is an excellent example of how clinical-radiologic-pathologic-molecular correlation plays into the landscape of molecular pathology to deliver optimal care for the patient.